Hortus Amoenus : Fasti, Flora y una poética espacial - Radiminski, Maricel Vanina (2018)
Estudiaremos el tratamiento de espacios como el locus amoenus y los jardines en el episodio dedicado a Flora en los Fasti ovidianos (5.183-378) a fin de determinar los alcances metapoéticos de estos escenarios.
I will study the treatment of spaces like the locus amoenus and the gardens in the episode dedicated to Flora in the Ovidian Fasti (V.183-378). I aim to point out the metapoetic reaches of these literary scenes.
Keywords: Ovidio; Fasti; Flora; Locus amoenus; Jardín; Ovid; Fasti; Flora; Locus amoenus; Garden; Análisis literario; Obras literarias; Poesía; Ovidio Nasón, Publio